Research notes and Documents collected by the late Prodyot Mukherjee, compiled by Arun Ghosh with editorial assistance from Sobhanlal Dutta Gupta, Indrani Ray, Occasional Paper No. 13, Centre for Studies in Social Sciences, Calcutta, 1977. - Agüero, Celma (Estudios de Asia y África, 1978)
-